Joint-ventures : uma ferramenta estratégica na internacionalização de PME portuguesas - Colaço, Diogo Fernandes (2013)
Despite the recent challenging economic environment, the SMEs have retained their position as the backbone of the European economy. Similar scenario can be found in Portugal, where SMEs have assumed a primary role and helped increasing the national export. Facing a deceleration in the European Common Market growth, both European and Portuguese SMEs have to redirect their activity toward new international markets and targets. Taking into consideration this scenario it’s important for SMEs to plan their internationalization strategy and chose the best tools for this purpose. Joint Ventures are frequently associated with large companies; nevertheless they have become a popular vehicle among SMEs and used as an effective and flexible tool in their internationalization programs. The formation of a Joint-venture allows SMEs to overtake bureaucratic, legal and financial barriers and at the same time to compete against larger corporations. This paper examines 14 Joint-ventures formed by Portuguese companies. Based on a questionnaire survey built for this purpose we intend to identify the main characteristics of these agreements, the factors that can lead to their success or failure, as well as the main reasons for Portuguese SMEs internationalization.